Implimentasi Sistem Bunga dan Bagi Hasil Terhadap Kinerja Keuangan Perbankan - Amin, Surahman (Tasamuh: Jurnal Studi Islam, 2019)
This research is aimed to know difference of the financial performance of the conventional banking and the syariah banking. Financial is measured by using ratios: ratio of capital to asset deliberated by according to risk, ratio of earning asset which classified to earning asset (KAP. I), ratio of allowance for possible earning losses to classified earning asset ( KAP.II), ratio of net operating income to operating income (NPM) representing proxy from management, ratio of profit before interest and tax to total asset ( ROA), ratio of operating expenses to operating income (BOPO), ratio of current assets to current liabilities and ratio of loan to deposit (LDR). This research use the saturated simple, that all bank of state of the public ownerships (BUMN) and bank of the Muamalat Indonesia, by using data of the secondary publicized by the Bank Indonesia each of semester, between period 2003-2011. The analysis instruments used was Multivariate Discriminant Analysis (MDA). Results of this research indicate that the CAMEL approach can determine banking financial performance. Pursuant to statistical test really there was financial performance difference between conventional banking and syariah banking, where conventional banking has better finance performance from syariah banking. This research found that CAR dan LDR; significantly differentiate conventional banking finance performance and syariah banking, in which the CAR was the most dominant